2010
DOI: 10.1186/cc9256
|View full text |Cite
|
Sign up to set email alerts
|

Year in review 2009: Critical Care - metabolism

Abstract: Novel insights into the metabolic alterations of critical illness were published in Critical Care in 2009. The association between early hypoglycaemia/high glycemic variability and poor outcome was confirmed. Improvements in the understanding of the pathophysiological mechanisms of stress hyperglycemia and potential progress in the bedside management of glucose control were presented. With regard to enteral nutrition, some alterations of gastrointestinal physiology were better delineated. The relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 44 publications
1
38
1
Order By: Relevance
“…After centrifugation, aliquots of the samples were immediately stored at −80°C before assay. Serum cortisol concentration was measured with a solid-phase, competitive chemiluminescent enzyme immunoassay in a calibrated IMMULITE 2000 analyzer (Diagnostic Products Corporation, Los Angeles, CA, USA).The normal range of morning serum cortisol concentration in our hospital laboratory is 145 to 650 nmol/L, which is broadly the same as that of other laboratories (201–681 nmol/L [21], 138–690 nmol/L [22], 119–618 nmol/L [12]). The detection limit was 5 nmol/L.…”
Section: Methodsmentioning
confidence: 56%
“…After centrifugation, aliquots of the samples were immediately stored at −80°C before assay. Serum cortisol concentration was measured with a solid-phase, competitive chemiluminescent enzyme immunoassay in a calibrated IMMULITE 2000 analyzer (Diagnostic Products Corporation, Los Angeles, CA, USA).The normal range of morning serum cortisol concentration in our hospital laboratory is 145 to 650 nmol/L, which is broadly the same as that of other laboratories (201–681 nmol/L [21], 138–690 nmol/L [22], 119–618 nmol/L [12]). The detection limit was 5 nmol/L.…”
Section: Methodsmentioning
confidence: 56%
“…This prospective cohort study is continued from our previous ones [14,15]. The data of 103 patients who completed both serum cortisol measurement and perioperative neuropsychological tests during the previous studies were included in the final analyses of this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Serum cortisol concentration was measured with a solid-phase, competitive chemiluminescent enzyme immunoassay in a calibrated Immulite 1000 analyzer (Diagnostic Products Corporation, Los Angeles, CA, USA) as in our previous study [14]. The intra-assay and inter-assay coefficients of variation were less than 5.6% and 8.2%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, there were strong positive correlations in day-by-day comparisons (P<0.001); therefore, we believe that CGMS glucose values are relatively accurate and reliable and can be used in STEMI patients undergoing p-PCI. Stress hyperglycemia is the result of sympathetic nervous system activation and increased production of catecholamines and cortisol that stimulate the processes of glyconeogenesis, glycogenolysis and lipolysis [33,34]. Goyal et al Data are reported as the mean ± SD or n (%).…”
Section: Discussionmentioning
confidence: 99%